The Outcomes of an e-Wellness Program for Lupus Patients in Thailand: A Participatory Action Research Approach - Nop T. Ratanasiripong; Steven Cahill; Christine Crane; Paul Ratanasiripong (Korean Society for Preventive Medicine, 2023)
Objectives Systemic lupus erythematosus (SLE) or lupus patients usually experience various physical and psychological challenges. Since the coronavirus disease 2019 pandemic, these challenges have become even harsher. Using the participatory action research approach, this study evaluated how an e-wellness program (eWP) impacted SLE-related knowledge and health behaviors, mental health, and quality of life among lupus patients in Thailand. Methods A 1-group, pretest-posttest design study was conducted among a purposive sample of lupus patients who were members of Thai SLE Foundation. The 2 main intervention components were: (1) online social support, and (2) lifestyle and stress management workshops. Sixty-eight participants completed all the study requirements, including the Physical and Psychosocial Health Assessment questionnaire. Results After being in the eWP for 3 months, participants' mean score for SLE-related knowledge increased significantly (t=5.3, p< 0.001). The increase in sleep hours was statistically significant (Z=−3.1, p<0.01), with the percentage of participants who slept less than 7 hours decreasing from 52.9% to 29.0%. The percentage of participants reporting sun exposure decreased from 17.7% to 8.8%. The participants also reported significantly lower stress (t(66)= −4.4, p<0.001) and anxiety (t(67)= −2.9, p=0.005). The post-eWP quality of life scores for the pain, planning, intimate relationship, burden to others, emotional health, and fatigue domains also improved significantly (p<0.05). Conclusions The overall outcomes showed promising results of improved self-care knowledge, health behaviors, mental health status, and quality of life. It is recommended that the SLE Foundation continues to use the eWP model to help the lupus patient community.